Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi pada Masyarakat RW 009 Kelurahan Bojong Menteng Bekasi 2018 - Maulitanisa, Hadistia (ARKESMAS [Arsip Kesehatan Masyarakat], 2019)
ABSTRACT Hypertension or often known as "high" is one of the non-communicable diseases, which is currently a big and serious problem. This study aims to determine the factors associated with the incidence of hypertension in RW 009 community in Bojong Menteng Bekasi Village in 2018. This research is analytic by using cross sectional study design. This research was conducted from January 2018 until July 2018 with a total sample of 161 people. The instruments used in this study were sphygmomanometer, microtoise, weight scales and questionnaires. Data analysis was carried out by univariate and bivariate using chi square test. The results of the study found 47.2% of respondents who experienced hypertension, who were at risk (?40 years) as much as 58.4%, male gender as much as 47.2%, history of family hypertension as much as 60.2%, obesity as much as 59 , 6%, smoking as much as 26.1%, less active physical activity by 53.4% and alcohol consumption by 1.2%. Furthermore, variables related to the incidence of hypertension were age (p = 0,000) PR 1,996 (95% CI: 1,334-2,986), history of family hypertension (p = 0,000) PR 3,197 (95% CI: 1,926-5,308), obesity (p = 0,000) PR 1,647 (95% CI: 1,264-2,145), smoking (p = 0,041) PR 1,473 (95% CI: 1,072-2,024), physical activity (p = 0,029) PR 1,495 (95% CI: 1,055- 2,118 ) Whereas, variables that were not related to the incidence of hypertension were sex (p = 0.252) PR 1.243 (95% CI: 0.896-1.724) and alcohol consumption (p = 1,000) PR 1.060 (95% CI: 0.263-4.280).The advice given to the puskesmas is that it is necessary to encourage the community, together with the head of RW 009 to raise awareness on routine health checks and routine exercise every holiday. Keywords: Hypertension, Factors that cause hypertension